Structural equivalence in a library and information science journal network in Taiwan - Chen, Ya-Ning (Malaysian Journal of Library and Information Science, 2019)
This study aimed to examine the hidden structures and patterns among Chinese-language library and information science (CLIS) journals in Taiwan according to structural equivalence of social network analysis. Thirteen CLIS journals and 3,150 articles published between 2001 and 2014 were selected as subject and a 13x13 matrix was aggregated for structural equivalence analysis. The matrix was reduced into 6x6 blocks, and their block matrices and image diagrams were created based on results of structural equivalence analysis. The six blocks (i.e., general LIS I and II, core LIS I and II, interdisciplinary and residual) were used to examine the journal positions, network images and core-peripheral structure in the network. The block structure of the CLIS journal network shows both stability and change through the two individual periods of seven years (i.e., 2001-2007 and 2008-2014). The structural equivalence based results provide valuable alternative publication outlets for paper re-submission for scholars when a paper has been rejected. Such result is useful for journal editors to gain an image of which journals are competitive rivals in terms of journal-to-journal citation network. The core-periphery structure is roughly supported by this study both for the overall fourteen years and during two individual periods.